1995
DOI: 10.1109/63.372601
|View full text |Cite
|
Sign up to set email alerts
|

An LCL resonant converter with PWM control-analysis, simulation, and implementation

Abstract: A three element resonant converter capable of driving voltage type load with load independent operation is analyzed using state-space approach. Pulse width modulation is employed to control and regulate the output voltage. Closed-form solutions are obtained under steady state conditions. The experimental study of a prototype converter reveals complete agreement with the analytical and SPICE simulation results. Typical experimental oscillograms are given to verify the basic principles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…It has been suggested to design Resonant Converter with three reactive components for better regulation. The LCL tank circuit based DC-DC SPRC has been experimentally demonstrated and reported by many researchers [1][2][3][4]. Mangesh B. Borage et al [5] have demonstrated the characteristics of LCL-T Resonant converter using Asymmetrical duty cycle (ADC).The converter operated at fixed resonant frequency and its analysised using state space approach.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested to design Resonant Converter with three reactive components for better regulation. The LCL tank circuit based DC-DC SPRC has been experimentally demonstrated and reported by many researchers [1][2][3][4]. Mangesh B. Borage et al [5] have demonstrated the characteristics of LCL-T Resonant converter using Asymmetrical duty cycle (ADC).The converter operated at fixed resonant frequency and its analysised using state space approach.…”
Section: Introductionmentioning
confidence: 99%
“…The design and development of various DC-DC resonant converters (RC) have been focused for telecommunication and aerospace applications in the recent past year, it has been found that these converters experience high switching losses, reduced reliability, electromagnetic interference (EMI) and acoustic noise at high frequencies. The LCL tank circuit based DC-DC converter have been experimentally demonstrated and reported in Raju and Doradla (1995) and Bhat (1994aBhat ( , 1997. It has been found from the literature that the LCL tank circuit has been connected in series with the load and operated in above resonant frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Resonant converters [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] are smaller in size and because of ZVS and/or ZCS operation, the switching losses are drastically reduced. Additional snubber components and heat sink are no longer required.…”
Section: Introductionmentioning
confidence: 99%
“…The PRC has the advantage of minimum components count but the major problem is that of poor part-load efficiency. Efforts to improve upon the basic PRC structure unearthed different multi elements Series-Parallel topologies [3,[7][8][9][10][13][14][15][16][17]. Extensive investigations have been conducted on this topologies but interestingly in many cases efforts towards providing guide line for better design in specific applications are missing in literature.…”
Section: Introductionmentioning
confidence: 99%